Pengaruh Media Pembelajaran Pop-Up Book Untuk Meningkatkan Hasil Belajar Siswa Kelas V SDN Cicayur 02 Bandung Pada Pelajaran IPA Materi Siklus Air - Damayanti, Gita; Yudiyanto, Mohamad; Nurishlah, Laesti; Samadi, Mochammad Ramdan (Prodi PGMI STAI Sabili Bandung, 2024)
This study evaluates the effectiveness of Pop Up Book media in enhancing the science learning outcomes of fifth-grade students at SDN Cicayur 02 Bandung, highlighting the necessity for innovative teaching methods that can boost student engagement and comprehension. Conducted from February 22 to March 8, 2024, the research employed a quantitative experimental model, comparing a class using Pop Up Books with a control class relying solely on textbooks and lectures. The t-test analysis revealed a significance value of 0.041, indicating a substantial difference between pretest and posttest results, with average student scores rising from 66.75 to 82.25, reflecting a 15.5% increase. Student response surveys revealed a high level of enthusiasm, averaging 90.75%. These findings underscore that Pop Up Book media is not only effective in improving learning outcomes but also enhances student motivation and involvement in the learning process.